Analisis Kepercayaan Merek Macbook Terhadap Loyalitas Konsumen - Christy Meivianty; Rita Widayanti (Ilmiah Manajemen Bisnis, 2014)
ABSTRACTConsumers consider many factors before making decision to purchase a certain product. One of the considered factor is the brand trust in the mind of consumer. The brand trust can be created if the brand can fulfill the need and satisfaction of the customer consistently. As a result, the consumer is always confidence with the any products of the trusted brand. The brand trust is very important factor in creating the loyalty of the consumer in purchasing any product from the trusted brand. The objective of the research was to determine the influence of brand trust MacBook Apple to the loyalty of the customer. The data from 100 respondents of id-mac community were analysed by using a simple regression analysis. The results of the study showed that the brand trust of MacBook Apple’s customer has a positive significant affect on customer loyalty. Therefore, it is adviced that MacBook Apple Manufacturers should increase the after sales service in order to maintain the customer’s loyalty.Keywords: Brand Trust, Customer Loyalty